High-Power Ultraflat Near-Infrared Supercontinuum Generation Pumped by a Continuous Amplified Spontaneous Emission Source - Aijun Jin; Hang Zhou; Xuanfeng Zhou; Jing Hou; Zongfu Jiang (IEEE Photonics Journal, 2015)
A high-power ultraflat near-infrared supercontinuum (SC) is generated in a section of photonic crystal fiber (PCF) pumped by an amplified spontaneous emission (ASE) source instead of continuous-wave (CW) and pulsed lasers. A low-power ASE seed at 1 μm is amplified to be 90.9 W by two fiber amplifiers and then emitted from a 10-μm-core fiber. Using this ASE source to pump a section of 100-m-long PCF, a 49.5-W near-infrared SC is obtained, and the 5-dB spectral bandwidth is 760 nm, covering from 1062 to 1822 nm. This is the reported highest power of ASE-pumped SC source. A comparative experiment is taken with a 122-W CW laser at 1090 nm to pump the same PCF. A 56.2-W SC source is generated with 5-dB spectral width of 605 nm from 1082 to 1687 nm. The conversion efficiency to SC is higher, and the spectrum is broader and flatter using the ASE source as the pump. Conclusively, pump incoherence can aid the SC generation and spectral flatness.